Knowledge and teaching practices in the context of remote emergency teaching in municipal early childhood education centers in Palmas -Tocantins - Batista , Idrlan Alves; Hirsch, Beatriz Inês Corteze; Silva , Maiara Sobral; Passos, Vânia Maria de Araújo (Seven Editora, 2023)
The covid-19 pandemic imposed the need for Emergency Remote Teaching (ERE) across the country. the constant teaching practices in the ludic pedagogical proposals that guided the families and guardians in carrying out the activities for the children, regarding their practicality, contextuality, accessibility and applicability, in order to verify whether the selection and articulation of the worked contents were structured with the practices teachers inserted in the mentioned documents and if they resulted in methodological referrals capable of instructing them to assume the role of protagonists of these practices. Thus, it appears that the Municipal Centers for Early Childhood Education in Palmas/TO are heading in the right direction, given that the pedagogical proposals are structured with practical, contextualized and easy-to-apply activities, as well as being available in a way that everyone can to have access. For this, it is based on bibliographical and documental reviews, whose purpose is to contribute with reflections and discussions related to the theme, as well as with the construction of alternatives that make it possible to improve the teaching practice, whether practiced by the teacher or by parents and guardians during the need. remote and/or hybrid teaching. DOI: https://doi.org/10.56238/devopinterscie-038